Cut-off analysis of HLA-A and HLA-B/C expression as a potential prognosticator of favorable survival in patients with metastatic breast cancer - Stefanovic, Stefan; Wirtz, Ralph; Sütterlin, Marc; Karic, Uros; Schneeweiss, Andreas; Deutsch, Thomas M.; Wallwiener, Markus (Anticancer research, 2023)
Background/Aim: Loss of differentiation of breast cancer cells in association with a down-regulated class I human leukocyte antigen (HLA) expression can lead to proliferation unhampered by cytotoxic T lymphocytes, which has been proven to be of prognostic relevance. The objective of this study was to determine the levels of HLA-A and HLA-B/C expression in metastatic breast cancer (MBC) cells and their usefulness for predicting 5-year survival. Materials and Methods: This prospective double-blinded cohort study analyzed patients starting a new line of therapy for MBC. RT-qPCR was used to determine the levels of HLA-A and B/C expression in MBC cells and the mRNA-based tumor intrinsic subtype. Two receiver operating characteristic curves (ROC) were constructed in order to determine whether HLA-A and HLA-B/C expression levels can be used for predicting 5-year survival. Youden J points, and sensitivity and specificity optimized cut-off points were determined for both ROC curves. Results: We enrolled 34 patients. The ROC curve for HLA-B/C had the highest AUC compared to HLA-A (0.55 vs. 0.42). High levels of HLA-A and HLA-B/C expression (40-ΔΔCT of 33.5 and 31.9, respectively) were highly specific (reaching 87.5% for HLA-A and even 100% specificity for HLA-B/C) yet insensitive for five-year survival in our study. Conclusion: High expression of certain class I HLA molecule subtypes by MBCs, in particular high HLA-A or B/C expression by MBC cells seems very specific in predicting the 5-year survival. We determined cut-off values for these HLA molecule clusters with high specificity, which might help identify patients with a favorable prognosis as prognosticators of a 5-year overall survival if their sensitivity is improved in larger prospective cohorts.
Gesehen am 21.06.2023